Effects of Climate Change Scenarios on Population and Distribution Pattern of Tree–Ferns in Nepal - Ripu M. Kunwar; Dipak Khadka; Khum Thapa‐Magar; Binaya Adhikari; Durga H. Kutal; Rama Ghimire; Komal R. Kafle; Sony Baral; Gokarna J. Thapa; Ananta Bhandari (Ecology and Evolution)
ABSTRACT By studying the population structure and spatial characteristics, the relationship between tree‐ferns and the environment can be reflected, which has high practical significance. In this study, we employed an ensemble distribution model to evaluate the relative contribution of various environmental variables and predict suitable habitats for tree‐fern across past, present, and future periods. Fieldwork was carried out between May–June 2019 and September 2022 in 11 districts of Nepal for population sampling and collecting the geocoordinates. Additional geocoordinates were collected from secondary sources such as previous literature, herbarium records, and online resources. We reported the occurrence of tree‐ferns from 28 districts within the altitudinal range of 300–2500 m. Longitudinally, the species is distributed only in central and eastern Nepal, with maximum density in central Nepal's Kaski and Lamjung districts. The central mid‐hills of Koshi and Gandaki provinces, particularly with the moist habitats and maximum rainfall, are suitable for the distribution of tree‐ferns. The projected distribution is influenced mainly by the mean temperature of the coldest quarter—Bio11 (34.9%), precipitation in dry months—Bio14 (34.5%), and mean annual temperature—Bio1 (33.9%). Climate extreme variables (maximum temperature in warmest months—Bio5, minimum temperature in coldest months—Bio6, precipitation in wettest months—Bio13, precipitation in wettest quarter—Bio16) contract the future distribution of species. The result portrays an expansion of suitable habitat for tree‐ferns while minor contractions are predicted in four districts of Bagmati province. As the Gandaki province receives the highest rainfall and the Koshi province has rich soil moisture, and precipitation plays a significant role in distribution, humid riverine places of Koshi and Gandaki support tree‐fern populations. Tree‐ferns could be an indicator species of the moist and humid climate. Given the extensive distribution in Nepal, India, and China, sustainable conservation of tree‐ferns through a species conservation action plan holds broader implications.